(untitled) (Journal of Informatics Education and Research, 2026)
This study aimed to review the fundamental shifts in the diagnosis and treatment of Post-Traumatic Stress Disorder (PTSD) amidst rapid technological advancements between 2010 and 2026. The research focused on examining neurobiological mechanisms and clinical innovations, such as Virtual Reality Exposure Therapy (VRET) and digital phenotyping. Adhering to the PRISMA protocol, a systematic review methodology was employed, analyzing 17 pivotal studies from Scopus and PubMed databases, including systematic reviews and randomized controlled trials (RCTs). Accordingly, the study reached the following key findings : Main Findings & Conclusion Efficacy of Modern Technologies: Virtual Reality Exposure (VRE) therapy demonstrated a significant superiority in reducing avoidance symptoms among PTSD patients, with a 30% faster response rate compared to traditional imaginal exposure. Digital Prediction: Artificial Intelligence algorithms and digital biomarkers showed the capability to predict relapse episodes 24 hours before their occurrence, with an accuracy rate of up to 80%. Resilience and Growth: A positive correlation was identified between digital social support and the enhancement of "Post-Traumatic Growth" (PTG), which subsequently reduces the severity of ruminative symptoms. Ethical Challenges: A gap has emerged between rapid technological evolution and the ethical legislation governing the privacy of sensitive psychological patient data. The study concludes with the necessity of adopting a "Hybrid Therapy" model that integrates digital technologies as adjunctive tools within traditional clinical settings. Furthermore, it recommends updating ethical protocols to keep pace with clinical digitization.